3D printed bandpass filters using compact high‐Q hemispherical resonators with improved out‐of‐band rejection. Issue 6 (1st March 2017) - Li, Jin; Guo, Cheng; Mao, Lijian; Xu, Jun
Abstract : RF design and implementation of ceramic‐filled resin‐based 3D printed millimetre‐wave bandpass filters (BPFs) using a new class of compact high‐quality‐factor hemispherical cavity resonators are addressed. Design concept of the hemispherical resonator is discussed for BPF applications in both X and Ka bands. For validation purpose, the Ka ‐band fourth‐order BPF is fabricated with a high‐temperature‐resistant ceramic‐filled resin using a fast and low‐cost stereolithography‐based 3D printing technique, and its surface metallisation is realised by employing electroless copper/silver plating. The proposed BPF's geometrical configuration contributes to a significantly improved out‐of‐band rejection. The RF‐measured results demonstrate the Ka ‐band BPF an insertion loss of 0.43−0.9 dB from 31.52 to 32.42 GHz, a passband return loss mostly better than 15 dB, and a small frequency shift of about 0.06%.